Psychosexual Outcome, Sexual Function, and Long-Term Satisfaction of Adolescent and Young Adult Men After Childhood Hypospadias Repair. Issue 9 (19th May 2020) - Tack, Lloyd J.W.; Springer, Alexander; Riedl, Stefan; Tonnhofer, Ursula; Weninger, Julia; Hiess, Manuela; Van Laecke, Erik; Hoebeke, Piet; Spinoit, Anne-Françoise; Cools, Martine; Van Hoecke, Eline
Abstract: Background: The psychosexual outcome in adolescents and young adults (AYA) men born with hypospadias is precarious. However, the factors responsible for impaired outcome in some AYA men have been understudied. Aim: To explore the outcome after hypospadias repair in childhood of AYA men aged 16–21 years and examine their opinion and their parents' opinion about this type of surgery. Methods: Cross-sectional assessment of 193 AYA men born with hypospadias and 50 male controls was performed. Questionnaires such as the Decision Regret Scale, Pediatric Penile Perception Score, Sexual Quality of Life–Male, International Index of Erectile Function, and a custom-made questionnaire were used. The Decision Regret Scale and a custom-made questionnaire were also completed by the participants' parents. Physical examination including Hypospadias Objective Penile Evaluation and measuring stretched penile length was performed. Outcomes: This study reports the psychosexual functioning (ie, social, relational, and sexual), erectile and sexual function after childhood hypospadias repair, using ad hoc measures. In addition, the opinion about hypospadias repair of patients and their parents is represented. Results: The number of surgeries and satisfaction regarding penile appearance were the most important factors associated with the opinion on hypospadias repair and the psychosexual outcome. Most AYA men were more satisfied with their penile appearance than the physician. 80% of men were satisfied with having had a childhood hypospadias repair, even though they had not been able to consent to surgery themselves. Erectile and ejaculation problems were mild and seen in approximately 10% of the population. Clinical Implications: Based on our data, deferring hypospadias repair until the patient can decide himself is not warranted. However, physicians who accept a suboptimal esthetic outcome and withdraw from repeated surgery may contribute importantly to the patient's well-being, especially in proximal forms of hypospadias. Strengths & Limitations: This is one of the rare studies addressing the AYA's psychosexual outcome after childhood hypospadias repair. Strengths include the combination of clinical and psychosexual data from a very large cohort of men and their parents to provide a more holistic view. By entering this study, participants might have a different comfort level regarding their sexuality or have a different body image than the overall population of young men. Conclusion: Uncomplicated hypospadias surgery results in equal psychosexual outcome as controls and in high satisfaction rates; multiple surgeries are a risk factor for poorer outcomes. 80% of men are satisfied with childhood hypospadias repair.